2011
DOI: 10.1103/physrevstab.14.111003
|View full text |Cite
|
Sign up to set email alerts
|

Response of colliding beam-beam system to harmonic excitation due to crab-cavity rf phase modulation

Abstract: During 2008 and 2009 dedicated beam experiments with crab cavities were performed in the KEKB. The goal was to measure the impact of crab-cavity radio frequency (rf) noise on the beam quality. These experiments were performed as a validation of the crab-cavity beam dynamics models in view of the possible use of crab cavities in the upgrade of the CERN Large Hadron Collider (LHC). An unexpected strong beam-beam instability was observed during the course of the experiments as a kind of frequency response. Unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Future directions of this work also include studies of the effect of different tune distributions on the achieved growth rates in the presence of damper, in particular for the expected distribution due to HOBB effects. Past literature has shown that in the case of dipole kicks or very short bunches, part of the excitation noise is converted in a coherent π-mode oscillation ( [2,4]). This oscillation should be strongly damped by the transverse damper in the case of phase noise-which results in an ensemble displacement of the bunch-but not with amplitude noise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future directions of this work also include studies of the effect of different tune distributions on the achieved growth rates in the presence of damper, in particular for the expected distribution due to HOBB effects. Past literature has shown that in the case of dipole kicks or very short bunches, part of the excitation noise is converted in a coherent π-mode oscillation ( [2,4]). This oscillation should be strongly damped by the transverse damper in the case of phase noise-which results in an ensemble displacement of the bunch-but not with amplitude noise.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of momentum kicks on the transverse emittance growth has been studied and measured before. Crab cavity tests at KEK [1] have shown the beam sensitivity to crab cavity rf noise [2]. Contrary to the HiLumi LHC though, these tests were conducted with a lepton beam, which has a very short synchrotron radiation damping time, focused on rf noise with a single spectral line, and were dominated by a π-mode instability.…”
Section: Introductionmentioning
confidence: 99%
“…We will not spend much time in this dissertation looking into detail at all the mechanisms that contribute to the reducing factor, or simply restrict the luminosity by setting limits (like the tune shift limits given by beam-beam or space-charge effects) [20,21]. We will simply use as an example of these mechanisms the luminosity degradation due to beam deformations, or the so called hourglass effect, and eventually, we will take a more detailed look at the luminosity degradation due to the crossing angle.…”
Section: Luminosity Degradationmentioning
confidence: 99%
“…), and the total crabbing angle can be built up turn by turn, allowing to lower the voltage per cavity as well as the total number of cavities. However, this scheme can considerably reduce the beam lifetime if it builds up resonant instabilities induced by harmonic excitations[20]. Further complications can derive from the fact that the global scheme requires that the bunches perform transverse oscillations, following the ring's betatron function on the crabbing plane along the machine.…”
mentioning
confidence: 99%
“…However, it will be added here as a perturbation after considering synchrotron radiation damping and emittance growth from luminosity burn-off. In this study we neglect the possible effects from dynamic aperture [17], beam scraping [18], and beam excitations from power converter noise, flux jumps, or crab cavity noise [15,[19][20][21]. To evaluate the intensity loss from luminosity production the total cross section of the proton is used as a pessimistic approximation.…”
Section: Introductionmentioning
confidence: 99%